Pathogen shifts in a honeybee predator following the arrival of the Varroa mite. Issue 1894 (9th January 2019) - Loope, Kevin J.; Baty, James W.; Lester, Philip J.; Wilson Rankin, Erin E.
Abstract : Emerging infectious diseases (EIDs) are a global threat to honeybees, and spillover from managed bees threaten wider insect populations. Deformed wing virus (DWV), a widespread virus that has become emergent in conjunction with the spread of the mite Varroa destructor, is thought to be partly responsible for global colony losses. The arrival of Varroa in honeybee populations causes a dramatic loss of viral genotypic diversity, favouring a few virulent strains. Here, we investigate DWV spillover in an invasive Hawaiian population of the wasp, Vespula pensylvanica, a honeybee predator and honey-raider. We show that Vespula underwent a parallel loss in DWV variant diversity upon the arrival of Varroa, despite the mite being a honeybee specialist. The observed shift in Vespula DWV and the variant-sharing between Vespula and Apis suggest that these wasps can acquire DWV directly or indirectly from honeybees. Apis prey items collected from Vespula foragers were positive for DWV, indicating predation is a possible route of transmission. We also sought cascading effects of DWV shifts in a broader Vespula pathogen community. We identified concurrent changes in a suite of additional pathogens, as well as shifts in the associations between these pathogens in Vespula . These findings reveal how hidden effects of the Varroa mite can, via spillover, transform the composition of pathogens in interacting species, with potential knock-on effects for entire pathogen communities.